Buddhism and an ageing society in Thailand as a part of Suvarnabhumi land - Watana, Somboon (Poligrafi, 2022)
Thailand is a country in Southeast Asia that was once Suvarnabhumi land with a long history of 2600 years in parallel with the history of Buddhism here. Buddhi-sm, the major religion in Thailand, was originally propagated by two Indian Budd-hist monks named Sona and Uttara. Consequently, Buddhism has contributed to the Thai people for a long time. Obviously, in the first quarter of the 21st century, the situation of the elderly population around the world has been monitored and planned. Thailand is a country in Southeast Asia that has had an Ageing Society for more than 10 years. About 93.5% of the Thai population believe in Buddhism. According to Buddhism, elderly people are valuable because of their experience and contribution, and Buddhism always teaches gratitude. Therefore, to meet the challenge of an ageing society, appropriate age-related caregiving must be subject to accountability. In the Pali Canon of Buddhism, there are many stories and tea-chings about the role and significance of elderly people along with caregiving, such as parents’ caregiving. The Buddha’s teachings have aimed to help provide human beings with physical, moral, emotional and wisdom development for the sake of their well-being. To follow the Buddha’s compassion, Buddhism in Thailand has been interpreted and applied to the well-being of ageing people.
Keywords: ageing society; Buddhism; budizem; religije; religion; starajoča se družba; starostniki; Suvarnabhumi; Tajska; Thailand